IMPACT OF ANTHROPOGENIC ACTIVITIES ON NATURAL RESOURCES: SEARCHING FOR SUSTAINABLE DEVELOPMENT MODELS - Iliuk, Наталя; Kostenko, Ігор; Bidolakh, Дмитро (Biota. Human. Technology, 2024)
Human activity continues to exert significant pressure on natural resources, creating considerable challenges for sustainable development. This article examines the multifaceted impact of human activity on natural resources and explores the search for models of sustainable development. The relevance of this topic lies in its significance for global ecological balance, socio-economic stability, and the well-being of present and future generations. The aim of this research is to analyze the complex relationships between anthropogenic activity and natural resources to identify effective strategies for achieving sustainable development. Methodology. In the course of writing this paper, a review of contemporary scientific research on the relevant topic was conducted. The following methods were applied in the work: analysis, systematization, generalization, and comparison. Scientific novelty. Through comprehensive research and analysis, this study reveals various aspects of anthropogenic impact on natural resources, including habitat destruction, pollution, overexploitation, and climate change. Existing models of sustainable development are examined, including ecological technologies, conservation measures, and legislative frameworks, highlighting their strengths and weaknesses, as well as their potential for scalability. The research findings emphasize the need for comprehensive approaches that integrate ecological, social, and economic aspects to mitigate anthropogenic pressures and promote sustainable management of natural resources. The study also highlights the importance of interdisciplinary collaboration, engagement of stakeholders, and global cooperation in advancing the sustainable development agenda. Conclusions. Based on these results, the research concludes that despite significant progress in understanding and addressing the impact of anthropogenic activities on natural resources, much remains to be done to achieve true sustainability. It underscores the need for transformative changes in production, consumption, and management models to protect ecosystems, enhance their resilience, and ensure equitable access to resources.